Evaluation of maSSS/maSES-PEG2-RM26 for their potential therapeutic use after labeling with Re-188. Could their [99mTc]Tc-labeled counterparts be used to estimate dosimetry? - Panagiotis Kanellopoulos; Quanyi Yu; Abouzayed Abouzayed; Ekaterina Bezverkhniaia; Vladimir Tolmachev; Anna Orlova (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Gastrin releasing peptide receptor (GRPR)-directed radiopharmaceuticals for targeted radionuclide therapy may be a very promising addition in prostate and breast cancer patient management. Aiming to provide a GRPR-targeting theranostic pair, we have utilized the Tc-99m/Re-188 radiometal pair, in combination with two bombesin based antagonists, maSSS-PEG2-RM26 and maSES-PEG2-RM26. The two main aims of the current study were (i) to elucidate the influence of the radiometal-exchange on the biodistribution profile of the two peptides and (ii) to evaluate the feasibility of using the [99mTc]Tc labeled counterparts for the dosimetry estimation for the [188Re]Re-labeled conjugates. Results Both peptides were successfully labeled with Re-188 and evaluated both in vitro and in vivo. In GRPR expressing PC-3 cells, both [188Re]Re-labeled peptides displayed high cellular uptake (8.5 ± 0.1% and 5 ± 0.3% of added activity, respectively), heavily GRPR-driven, while retaining the radioantagonistic profile with slow internalization rates. Both agents demonstrated high receptor affinity when loaded with natRe (7.5 nM and 8 nM, respectively). When tested in vivo in GRPR expressing PC-3 xenografts, both radioantagonists demonstrated high tumor accumulation (6.3 ± 0.5%IA/g and 5 ± 1%IA/g at 1 h pi, respectively), with good retention over time (4 ± 2%IA/g and 3.1 ± 0.1%IA/g at 4 h pi, respectively). In addition, their biodistribution profiles were closely mimicking their [99mTc]Tc-labeled counterparts. Statistically significant lower tumor uptake was found for both conjugates labeled with Tc-99m, which may result in underestimation of the dose delivered to the tumor. Conclusions All the results indicate that Tc-99 m could be used for dosimetry evaluation for the two [188Re]Re-labeled radioligands, with minimal alterations in their biodistribution pattern and tumor targeting capabilities.